1981
DOI: 10.1093/ptj/61.10.1419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isometric Muscle Training on Residual Limb Volume, Strength, and Gait of Below-Knee Amputees

Abstract: This study was undertaken to determine if prosthetic suspension capabilities of below-knee amputees could be improved by using biofeedback in a controlled exercise program. Improvements in muscle bulk of four amputees were assessed. Changes in transverse cross-sectional areas and suspension ability of the residual limb were measured. The effect of muscle training on gait and on muscle-use patterns during gait was observed. Marked increases in muscle bulk below the knee and improvement in suspension capabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Amputee gait has been evaluated both qualitatively (Gonzalez et al, 1974;Urban 1973; Waters et al, 1976; Kegel et al, 1981) and quantitatively in the literature. Quantitative fesearch can be further subdivided into kinematic and kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Amputee gait has been evaluated both qualitatively (Gonzalez et al, 1974;Urban 1973; Waters et al, 1976; Kegel et al, 1981) and quantitatively in the literature. Quantitative fesearch can be further subdivided into kinematic and kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other domains of physical rehabilitation [16][17], the field of prosthetics has paid little attention to the translation of well-established motor learning strategies [18][19][20]. Instead, physical rehabilitation for individuals with lower limb loss has traditionally focused on what tasks to practice [21][22][23][24] and which strength and conditioning exercises to perform [25][26][27][28][29], rather than on how motor learning principles should be applied to the structure and organization of practice in order to most efficiently and effectively learn those tasks. The current state of prosthetic research also reflects this priority.…”
Section: Introductionmentioning
confidence: 99%
“…However, this control depends on the function of the muscles in the trans-tibia1 stump and the patient's ability to activate and control them. Kegel et al (1981) have shown that exercise of the stump musculature should be a part of routine physical therapy. The amputees must be able to control fully the musculature during gait.…”
Section: Introductionmentioning
confidence: 99%